Characteristics Of Sales And Purchase Agreement Of Flats With Pre Project Selling System With Criminal Effect - Liliana Sysylia Darmono; Miftakhul Huda (JURNAL HUKUM SEHASEN, 2024)
This research explores the characteristics of apartment sale and purchase agreements with a pre-project selling system which have the potential to give rise to criminal consequences. The pre-project selling system is becoming a trend in the property industry, where property units are sold before the construction project begins. This research discusses how the characteristics of apartment sale and purchase agreements with this system can contribute to the potential for criminal acts to occur. The research method involves analysis of treaty documents, related legislation, and case studies related to criminal law. The research results highlight critical aspects of the agreement, such as unclear clauses, payment of large amounts before the project begins, and uncertainty over the project completion period. Possible criminal legal implications include fraud, embezzlement, or violations of consumer protection laws. Therefore, this research provides an in-depth understanding of the characteristics of apartment sale and purchase agreements with a pre-project selling system and highlights the need for increased regulation and legal protection to protect consumer interests and prevent potential criminal acts in such property transactions.